The wildest race ever : the story of the 1904 Olympic marathon - McCarthy, Meghan (Simon & Schuster/Paula Wiseman Books, 2016)
"The exciting and bizarre true story of the 1904 Olympic marathon, which took place at the St. Louis World's Fair."--